2004
DOI: 10.5301/jbm.2008.4693
|View full text |Cite
|
Sign up to set email alerts
|

Discordant results obtained for different methods of HER-2/neu testing in breast cancer a question of standardization, automation and timing

Abstract: The concordance between conventional IHC and computerized analysis was very good. The number of patients with stage IV breast cancer with an elevated sHER-2/neu level was much higher than HER-2/neu positivity in tissue. This discrepancy is only partially explained by the influence of tumor load. Patients with an elevated sHER-2/neu level and no tissue overexpression should be considered for retesting of tissue or a new biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Studies have shown that serum HER2 levels, prior to treatment, positively correlate with tumor size, number of positive lymph nodes and histological scores [25]. In fact, serum HER2 levels were a better indicator for stage IV breast cancer than were IHC scores [26]. Serum HER2 levels were also an effective prognostic indicator for metastasis-free and disease-specific survival after treatment cessation [25].…”
Section: Her2mentioning
confidence: 99%
“…Studies have shown that serum HER2 levels, prior to treatment, positively correlate with tumor size, number of positive lymph nodes and histological scores [25]. In fact, serum HER2 levels were a better indicator for stage IV breast cancer than were IHC scores [26]. Serum HER2 levels were also an effective prognostic indicator for metastasis-free and disease-specific survival after treatment cessation [25].…”
Section: Her2mentioning
confidence: 99%
“…
When combined with estradiol or progesterone receptor status, patients with elevated serum ERBB2 ECD (sERBB2) and receptor-negative tumors had a significantly shorter disease-specific survival (4). The strong positive correlation observed between sERBB2 levels and ERBB2 amplification assessed by FISH technique have led researchers to conclude that patients with an elevated sERBB2 level and no tissue overexpression should be considered for retesting of tissue material or a new biopsy (5,6).One of the key roles of ERBB2 oncogene is in the modulation of the cellular response to cytotoxic and inflammatory cytokines (7), which are excessively produced by cancer tissues (8). Cytokines have been used as biomarkers in research for prognosis and have been associated with symptoms and adverse outcomes in breast cancer.
…”
mentioning
confidence: 99%
“…When combined with estradiol or progesterone receptor status, patients with elevated serum ERBB2 ECD (sERBB2) and receptor-negative tumors had a significantly shorter disease-specific survival (4). The strong positive correlation observed between sERBB2 levels and ERBB2 amplification assessed by FISH technique have led researchers to conclude that patients with an elevated sERBB2 level and no tissue overexpression should be considered for retesting of tissue material or a new biopsy (5,6).…”
mentioning
confidence: 99%